Traumatic Vulvar Epithelial Inclusion Cysts Following Female Genital Mutilation (FGM) - Mack-Detlefsen, B.; Banaschak, S.; Boemers, T. M. (Geburtshilfe und Frauenheilkunde, 2015)
Background: Female genital mutilation (FGM) occurs mainly in Africa, parts of the Arabian Peninsula and parts of Asia. It is commonly associated with acute complications as well as diverse late/delayed complications. One of the most common of these late complications is progressively enlarging painless cysts of the vulva. Case Report: An 8-year-old girl from Eritrea presented to our paediatric emergency department with a progressively enlarging mass of the vulva. She had undergone a clitoridectomy and partial removal of the labia minora as an infant in Eritrea. We performed surgical excision of the cyst and reconstruction of the labia. Histology showed a traumatic squamous epithelial inclusion cyst of the vulva. Conclusion: Epithelial or dermoid cysts of the vulva following FGM are extremely rare. Symptoms often require surgical intervention. Through increasing migration, more girls and female youths with FGM are likely to present to practices and hospitals in Germany. Thus increased knowledge and awareness of the medical complications of FGM and their treatment will be necessary in years to come.
Keywords: adolescence; benign tumours of the vulva; dysuria